2014
DOI: 10.1166/jnn.2014.10092
|View full text |Cite
|
Sign up to set email alerts
|

TiO<SUB>2</SUB> Particles on a 3D Network of Single-Walled Nanotubes for NH<SUB>3</SUB> Gas Sensors

Abstract: Ammonia (NH3) gas is one of the gases which causes damage to environment such as acidification and climate change. In this study, a gas sensor based on the three-dimensional (3D) network of single-walled nanotubes (SWNTs) was fabricated for the detection of NH3 gas in dry air. The sensor showed enhanced performance due to the fast gas diffusion rate and weak interactions between the carbon nanotubes and the substrate. Metal oxide particles were introduced to enhance the performance of the gas sensor. Atomic la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Titanium dioxide (TiO 2 ) has been widely used in the field of environmental protection and energy conservation such as photocatalysis, , heterogeneous catalysis, ,, gas sensors, and dye-sensitized solar cells due to its excellent photoelectric properties, nontoxic nature, physical chemical stability, high catalytic activity, and low costs. Au nanoparticles supported on TiO 2 have been widely used in many important catalytic reactions. , The structures of Au nanoparticles on TiO 2 have been studied using high-resolution electron microscopy (HREM), and researchers found that the catalytic activity strongly depends on the size of Au particles as well as the crystalline structure of TiO 2 supports. , Density functional theory (DFT) calculations were employed to investigate the interactions between Au and TiO 2 support as well as the reaction mechanisms for reactions catalyzed by Au/TiO 2 catalysts. , Catalytic hydrogenation is an important type of reaction in which Au nanoparticles supported on TiO 2 exhibit their particular catalytic capability such as in CO 2 reduction, ,,− the hydrogenation of unsaturated C–C bonds, ,, the selective hydrogenation of α,β-unsaturated carbonyl compounds such as aldehydes and ketones, ,, and the hydrodeoxygenation of biomass-derived compounds. ,,, In these hydrogenation processes, the adsorption and dissociation of hydrogen on the supported metal particles are crucial steps and sometimes rate-limiting .…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) has been widely used in the field of environmental protection and energy conservation such as photocatalysis, , heterogeneous catalysis, ,, gas sensors, and dye-sensitized solar cells due to its excellent photoelectric properties, nontoxic nature, physical chemical stability, high catalytic activity, and low costs. Au nanoparticles supported on TiO 2 have been widely used in many important catalytic reactions. , The structures of Au nanoparticles on TiO 2 have been studied using high-resolution electron microscopy (HREM), and researchers found that the catalytic activity strongly depends on the size of Au particles as well as the crystalline structure of TiO 2 supports. , Density functional theory (DFT) calculations were employed to investigate the interactions between Au and TiO 2 support as well as the reaction mechanisms for reactions catalyzed by Au/TiO 2 catalysts. , Catalytic hydrogenation is an important type of reaction in which Au nanoparticles supported on TiO 2 exhibit their particular catalytic capability such as in CO 2 reduction, ,,− the hydrogenation of unsaturated C–C bonds, ,, the selective hydrogenation of α,β-unsaturated carbonyl compounds such as aldehydes and ketones, ,, and the hydrodeoxygenation of biomass-derived compounds. ,,, In these hydrogenation processes, the adsorption and dissociation of hydrogen on the supported metal particles are crucial steps and sometimes rate-limiting .…”
Section: Introductionmentioning
confidence: 99%
“…To improve sensitivity and selectivity, biosensors that incorporate a variety of bioreceptors and transducers have been reported in the literature. SWNT surface can be functionalized/decorated with inorganic molecules (TiO 2 , SnO 2 nanoparticles) [24,25,26], organic macromolecules (porphyrin, polycyclic aromatic hydrocarbons) [27,28], or biomolecules [29] to improve the sensing performance. DNA molecules [30,31] are naturally occurring polymers that have many unique functions, including catalyzing chemical reactions [32] and controlling gene expression.…”
Section: Introductionmentioning
confidence: 99%